Chickenpox prevention behaviour in the Ras Laffan Industrial City Qatar - Djuhari Djuhari (University of Muhammadiyah Semarang, 2020)
Chickenpox is a highly contagious infectious disease caused by the Varicella Zoster virus, characterized by a characteristic eruption on the skin and can affect people of all ages. Increasing knowledge and behaviour to prevent chickenpox transmission is very important for mining workers, especially in their accommodation environment. The purpose of this study was to determine the relationship between knowledge of mining workers and prevention behaviour of chickenpox transmission. The type of research used is associative descriptive. The respondents of this study were 67 mining workers who lived in the Ras Laffan Industrial City Qatar accommodation, which were obtained through total sampling. The results showed that there was a relationship between knowledge and the behaviour to prevent chickenpox transmission with a significant value of p = 0.023, p <α (0.05). Suggestions for workers in the Ras Laffan Industrial City Qatar accommodation environment, especially those related to preventing the transmission of chickenpox, should be more aware of the very fast transmission of chickenpox.